Work Training Strategies and Policies to Reduce Open Unemployment in Ogan Komering Ulu Regency - Iwan Kurniawan (Jurnal Studi Pemerintahan dan Akuntabilitas, 2026)
Purpose: This study aims to assess the impact of vocational training programs on reducing the Open Unemployment Rate (TPT) in Ogan Komering Ulu Regency from 2020 to 2024. It examines the challenges faced in implementing these programs and proposes policy recommendations to enhance their effectiveness in the future. Research Methodology: This study uses a qualitative approach, analyzing data from regional development reports, training participation rates, and interviews with local officials and training providers to assess the success and challenges of existing vocational programs. Results: The findings show that while Ogan Komering Ulu Regency's TPT was generally lower than South Sumatra's provincial and national rates until 2024, there was a significant increase in 2024. The analysis highlights that limited training options, inadequate funding, and low worker participation are key factors that hinder the success of these programs. Conclusions: Vocational training programs have the potential to significantly reduce unemployment in the region, but their effectiveness is constrained by various factors. Policy recommendations include increasing funding, expanding training options, enhancing job placement initiatives, and improving communication and outreach for vocational training programs for people with disabilities. Limitations: The study is limited by the availability of data, particularly in terms of detailed tracking of vocational program graduates and their post-training employment outcomes. Further studies are needed to measure the long-term impact of vocational training on employment sustainability. Contribution: This study enhances the understanding of labor development policies in Ogan Komering Ulu Regency and provides recommendations for improving vocational training programs to reduce unemployment and support local workforce development.